Vanadium-based neutron transparent alloy material and preparation method thereof
By designing vanadium-based neutron transparent alloy materials, the problem of neutron signal interference in existing materials under high-pressure extreme conditions is solved, and the physical/chemical stability and mechanical properties of the materials are improved, ensuring the accuracy and reliability of neutron scattering experiments.
Patent Information
- Application Number
- CN202411316446.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-18
AI Technical Summary
The existing neutron transparent alloy materials cannot effectively solve the problem of neutron signal back bottom interference under high-pressure extreme conditions, and the physical/chemical stability and mechanical properties of the materials are insufficient.
A vanadium-based neutron transparent alloy material is designed with a chemical composition of V1-xMx, where x < 0.1, forming a disordered solid solution with a body-center cubic structure, and the metal M is selected from Al, Nb, Ta, Fe, Sn or Mo. The alloy is prepared by vacuum smelting and processing technology to ensure random distribution of V and M atoms, eliminate neutron diffraction peaks, and achieve neutron transparency.
The prepared vanadium-based neutron transparent alloy material has excellent physical/chemical stability and mechanical properties, which can effectively eliminate neutron diffraction peaks, improve the accuracy and reliability of neutron scattering experiments, and is low in cost and has a wide range of applications.
Smart Images

Figure CN119640118A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a neutron transparent alloy material, in particular to a vanadium-based neutron transparent alloy material and a preparation method thereof; and belongs to the technical field of new functional materials. Background Art
[0002] With the commissioning of domestic neutron source equipment, the study of the structural evolution of materials under high-pressure extreme conditions has become a new hot spot. Using a neutron scattering high-pressure spectrometer, not only can the microscopic morphological characteristics of the material be obtained, but also the position of the elements can be specifically analyzed, and the magnetic, electrical and optical characteristics of the material can be analyzed from an atomic perspective. Since neutrons can penetrate most known substances and produce obvious scattering signals that interfere with the signals of the measured substances, neutron scattering detection places higher requirements on the sample containers used for testing. An alloy that is transparent to neutrons (i.e., neutron transparent alloy) is required to provide important material support for neutron scattering technology. By utilizing the high penetration ability of neutrons in substances, the sample is placed in a sample container made of a neutron transparent alloy for neutron scattering research, and undisturbed sample data can be obtained, which greatly improves the accuracy and reliability of neutron scattering experimental detection.
[0003] The invention patent with application number 201610557297.0 discloses a vanadium-nickel alloy for preparing a neutron scattering experiment sample box and its application, the general formula of which is V x Ni y , wherein the atomic ratio of vanadium to nickel is x:y=(26.9±0.1):1. The alloy can be used as a material for preparing a sample box for a neutron scattering experiment. The vanadium-nickel alloy in which the atomic ratio of vanadium to nickel is (26.9±0.1):1 is used, so that the prepared sample box will hardly generate interference signal peaks in the detected test sample data, and the data quality of the neutron scattering experiment is more reliable and credible. The invention patent with application number 201510998659.5 discloses a molybdenum-titanium alloy neutron transparent material and a preparation method thereof, wherein the molybdenum content in the molybdenum-titanium alloy neutron transparent material is 46-56wt%, and the rest is titanium. This molybdenum-titanium alloy neutron transparent material has the characteristics of high strength, can increase the pressure of the high-pressure cavity, increase the number of high-pressure experimental samples, and reduce the cost of high-pressure testing.
[0004] There are not many studies on neutron transparent alloy materials in the prior art, and the developed materials cannot effectively solve the problem of neutron signal background interference when used as neutron diffraction high-pressure cavity gaskets. In recent years, reports have shown that titanium-zirconium alloy is a relatively ideal neutron transparent material. The invention patent with application number 202211047644.7 discloses a high-strength titanium-zirconium alloy neutron transparent material and its preparation method. It uses high-purity titanium powder and high-purity zirconium powder as basic raw materials, adopts the powder metallurgy method, and after isostatic pressing technology, vacuum sintering obtains a uniform and dense titanium-zirconium alloy. Later, a protective hot forging process is used to strengthen the body, and a high-strength neutron transparent titanium-zirconium alloy is obtained after straightening treatment. The preparation process of the present invention is concise and easy to implement. It is very suitable for high-quality and small-batch production. The strength of the prepared titanium-zirconium alloy exceeds that of high-purity vanadium, and the neutron background is uniform. It can be used for the preparation of high-intensity neutron scattering high-pressure pressure chamber to increase the pressure of neutron scattering experiments. It has been verified that Ti 2.08 Zr is currently the only material used in neutron scattering detection containers, but it will react with O2 above 200°C and with acid at room temperature. In addition, this material faces many disadvantages such as harsh and complex synthesis conditions, high price, and low alloy strength resulting in size limitations.
[0005] In view of the above reasons, it is urgent to develop a neutron-transparent alloy material with excellent physical / chemical stability and mechanical properties. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, one of the purposes of the present invention is to accurately design a neutron transparent alloy formula, thereby providing a vanadium-based neutron transparent alloy material;
[0007] The second purpose is to successfully prepare a variety of vanadium-based neutron-transparent alloy materials.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention first discloses a vanadium-based neutron transparent alloy, the chemical composition of which is V 1-x M x , wherein x is less than 0.1, the alloy is a disordered solid solution of a body-centered cubic structure composed of a single crystal phase, wherein V is the metal element vanadium, and M is selected from one or more of Al, Nb, Ta, Fe, Sn or Mo.
[0010] Preferably, the neutron diffraction spectrum of the aforementioned vanadium-based neutron transparent alloy does not have a Bragg diffraction peak between 50 and 160°.
[0011] Preferably, all metal atoms in the aforementioned vanadium-based neutron transparent alloy are randomly distributed at the same Wyckoff site.
[0012] Preferably, the purity of the metal V is higher than 99.95%, and the purity of the metal M is 99.99%.
[0013] Preferably, the neutron transparent alloy is composed of two elements, and the chemical formula is: V 0.9002 Al 0.0998 、V 0.9486 Nb 0.0514 、V 0.9476 Ta 0.0524 、V 0.9611 Fe 0.0389 、V 0.9421 Sn 0.0579 or V 0.946Im o 0.0539 .
[0014] Preferably, the neutron transparent alloy is composed of multiple elements, and the chemical formula is: V 0.902 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 、V 0.908 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Mo 0.02 、V 0.892 Nb 0.018 Ta 0.035 Al 0.001 Sn 0.026 Mo 0.019 、V 0.902 Nb 0.018 Ta 0.035 Fe 0.008 Sn 0.026 Mo 0.019 、V 0.917 Nb 0.018 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.02 or V 0.901 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.019 .
[0015] Preferably, the aforementioned neutron transparent alloys all have a body-centered cubic structure, and the space group is Im to 3m.
[0016] The present invention also discloses a method for preparing the aforementioned vanadium-based neutron-transparent alloy, comprising the following steps:
[0017] S1. Design the formula of vanadium-based neutron-transparent alloy;
[0018] S2, weighing and mixing: according to the vanadium-based neutron transparent alloy formula designed in step S1, accurately weigh the weight of metal V and metal M to obtain a vanadium-based neutron transparent alloy raw material;
[0019] S3, vacuum smelting to obtain alloy ingots: using a primary or secondary smelting process at 3000-3500°C in a protective atmosphere to obtain alloy ingots;
[0020] S4. Processing: The alloy ingot is processed to a suitable size by wire cutting and polished to a smooth surface.
[0021] Preferably, the aforementioned protective atmosphere is argon.
[0022] Preferably, in the preparation method of the aforementioned vanadium-based neutron-transparent alloy, if the metal M is Fe, Nb, Ta or Mo, a neutron-transparent alloy ingot is obtained by a one-step smelting process; if the metal M is Al or Sn, a two-step smelting process is adopted, firstly, a part of the ingredients are partially pre-melted to form a stable intermediate product, such as V 0.8 Ni 02 、V 0.5 Al 0.5 、V 0.8 Sn 0.2 Etc., and then melted with the remaining raw materials to obtain a neutron-transparent alloy ingot of target composition, ensuring that the chemical composition of the final product matches our design and has the neutron-transparent properties of coherent scattering.
[0023] The present invention is beneficial in that:
[0024] (1) The vanadium-based neutron-transparent alloy material V of the present invention 1-x M x The main material is vanadium, and the metal M is selected from one or more of Al, Nb, Ta, Fe, Sn or Mo. The material forms a disordered solid solution with a body-centered cubic structure, and the V and M atoms are randomly distributed at the vertices and the center of the body-centered cubic lattice. While not destroying the body-centered cubic crystal structure of metal vanadium, the neutron diffraction peak generated by metal vanadium can be effectively eliminated, and a neutron transparent alloy material is successfully prepared. The material has good neutron transparency and can be used as a raw material for producing neutron scattering experiment sample boxes.
[0025] (2) The alloy material formula has a variety of options. By accurately designing the alloy material formula and strictly controlling the synthesis conditions, a variety of new dual-element and multi-element vanadium-based neutron-transparent alloys are obtained. The composition is novel, the synthesis process is simple and controllable, and the energy consumption and cost are low. The surface of the vanadium-based neutron-transparent alloy ingot prepared by the arc melting process is flat and smooth, without any doping segregation and clustering, and the structure is uniform and stable, with a wide range of applications.
[0026] (3) The present invention is the first to produce a multi-element vanadium-based transparent neutron alloy, including: V 0.902 Nb 0.018 Ta 0.036 Al 0.0 1Fe 0.008 Sn 0.026 、V 0.908 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Mo 0.02 、V 0.892 Nb 0.018 Ta 0.035 Al 0.001 Sn 0.026 Mo 0.019 、V 0.902 Nb 0.018 Ta 0.035 Fe 0.008 Sn 0.026 Mo 0.019 、V 0.917 Nb 0.018 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.02 and V 0.901 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.019 During the synthesis, we found that Mo, Nb and Ta have high melting points, and the eutectic system can be used as a low-energy pathway to produce multi-component intermediates, which in turn helps to obtain the above-mentioned multi-element vanadium-based neutron-transparent alloy with excellent performance.
[0027] (4) The vanadium-based neutron-transparent alloy material prepared by the present invention also has excellent chemical and mechanical properties. 2.08Zr alloys have better high-temperature chemical stability. In particular, multi-element HEV alloys have stronger oxidation resistance than any single-dopant vanadium-based alloys and have the highest engineering yield performance. It can be seen that multi-element doped neutron-transparent alloys exhibit more outstanding chemical stability and excellent mechanical properties, providing more directions for the design of neutron-transparent alloy materials with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a structural simulation diagram of the neutron transparent alloy prepared in Example 1 of the present invention, wherein red represents V atoms and blue represents M atoms;
[0029] Figure 2 is a sample diagram of a neutron-transparent alloy ingot obtained in Examples 1 to 6 of the present invention;
[0030] Figure 3 is a comparison diagram of XRD of neutron transparent alloys prepared in Examples 1 to 6 of the present invention;
[0031] Figure 4 is the XRD diagram of the neutron transparent alloys prepared in Examples 1 to 6 of the present invention;
[0032] Figure 5 is the XRD diagram of the neutron transparent alloys prepared in Examples 7 to 12 of the present invention;
[0033] Figure 6 is a high-resolution neutron diffraction pattern of the neutron-transparent alloys prepared in Examples 1 to 6 of the present invention;
[0034] Figure 7 is a high-resolution neutron diffraction pattern of the neutron-transparent alloys prepared in Examples 7 to 12 of the present invention;
[0035] Figure 8 The neutron transparent alloys prepared in Examples 1 to 6 of the present invention are Rietveld refinement of synchrotron X-ray diffraction at monochromatic wavelength;
[0036] Fig. 9 The neutron transparent alloys prepared in Examples 7 to 12 of the present invention are Rietveld refinement of synchrotron X-ray diffraction at monochromatic wavelength;
[0037] Fig.10 is an optical microscopic image of the neutron transparent alloys prepared in Examples 1 to 6 of the present invention at 1000 times magnification;
[0038] Fig.11 is an optical microscopic image of the neutron transparent alloys prepared in Examples 7 to 12 of the present invention at 1000 times magnification;
[0039] Fig.12 is a small-angle neutron scattering diagram of the neutron-transparent alloys prepared in Examples 1 to 6 of the present invention;
[0040] Fig.13 is a small-angle neutron scattering diagram of the neutron-transparent alloys prepared in Examples 7 to 12 of the present invention;
[0041] Fig.14 is a TGA / DSC graph of the neutron transparent alloys prepared in Examples 1 to 6 of the present invention;
[0042] Fig.15 is a TGA / DSC graph of the seed transparent alloy prepared in Example 7 of the present invention;
[0043] Fig.16 This is a standard dumbbell-shaped sample diagram cut from the neutron transparent alloys prepared in Examples 7 to 12 of the present invention;
[0044] Fig.17 is a strain-stress characteristic curve of the neutron transparent alloys prepared in Examples 1 to 6 of the present invention;
[0045] Fig.18 3 is a graph showing strain-stress characteristic curves of the neutron transparent alloys prepared in Examples 7 to 12 of the present invention. DETAILED DESCRIPTION
[0046] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0047] Unless otherwise specified in the present invention, all raw materials used are commercially available. Among them, the purity of metal V is higher than 99.95%, and the purity of metal M (Al, Nb, Ta, Fe, Sn and Mo) is 99.99%. All raw materials can be used directly without purification.
[0048] Examples 1 to 6 are single-element doped V-based transparent neutron alloys; Examples 7 to 12 are multi-element doped V-based transparent neutron alloys.
[0049] Example 1
[0050] This embodiment adopts a two-step arc melting method, the melting atmosphere is argon, the temperature is 3000-3500°C, and the first step is to form an intermediate V 0.5 Al 0.5 The molar ratio of V and Al raw materials is 1:1. In the second step, V metal is added and melted again to obtain the target alloy V 0.9002 Al 0.0998 .
[0051] In this embodiment, since the melting point of the doped metal Al is relatively low and the melting point of vanadium is quite high, the two-step arc melting method can ensure that the chemical composition of the final product matches our design, giving the material the neutron transparent property of coherent scattering.
[0052] Example 2
[0053] In this embodiment, the target alloy V is prepared by a one-step arc melting method. 0.9486 Nb 0.0514 The smelting atmosphere is argon and the temperature is 3000-3500℃.
[0054] Example 3
[0055] This embodiment is the same as embodiment 2, and the target alloy V is obtained by a one-step arc melting method. 0.9476 Ta 0.0524 .
[0056] Example 4
[0057] This embodiment is the same as embodiment 2, and the target alloy V is obtained by a one-step arc melting method. 0.9611 Fe 0.0389 .
[0058] Example 5
[0059] This embodiment is the same as embodiment 1, and adopts a two-step arc melting method to first form an intermediate V 0.8 Sn 0.2 In the second step, the target alloy V is obtained. 0.9421 Sn 0.0579 .
[0060] Example 6
[0061] This embodiment is the same as embodiment 2, and the target alloy V is obtained by a one-step arc melting method. 0.946Im o 0.0539 .
[0062] Table 1 lists the chemical compositions of the vanadium-based neutron-transparent alloys prepared in Examples 1 to 6, the main part of which is V, and the atomic percentage of V reaches more than 90%.
[0063]
[0064] Table 1 Chemical composition and atomic content of dual-element vanadium-based neutron-transparent alloy
[0065] Example 7
[0066] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate Nb-Al-Fe-Sn under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate and the melting is repeated for 5 times under an argon atmosphere at a melting temperature of 3000-3500°C to obtain the target alloy HEV1 of this embodiment, i.e., V 0.902 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 .
[0067] Example 8
[0068] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate V-Nb-Ta-Mo under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate, and the melting is repeated for 5 times under an argon atmosphere to obtain the target alloy HEV2 of this embodiment, i.e., V 0.908 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Mo 0.02 .
[0069] Example 9
[0070] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate V-Nb-Ta-Mo under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate, and the melting is repeated for 5 times under an argon atmosphere to obtain the target alloy HEV3 of this embodiment, i.e., V 0.892 Nb 0.018 Ta 0.035 Al 0.001 Sn 0.026 Mo 0.019 .
[0071] Example 10
[0072] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate V-Nb-Ta-Mo under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate, and the melting is repeated for 5 times under an argon atmosphere to obtain the target alloy HEV4 of this embodiment, i.e., V 0.902 Nb 0.018 Ta 0.035 Fe 0.008 Sn 0.026 Mo 0.019 .
[0073] The alloy material prepared in this embodiment has optimal engineering yield properties.
[0074] Embodiment 11
[0075] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate V-Mo-Nb under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate, and the melting is repeated for 5 times under an argon atmosphere to obtain the target alloy HEV5 of this embodiment, i.e., V 0.917 Nb 0.018 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.02 .
[0076] Example 12
[0077] In this embodiment, a two-step arc melting method is used to repeatedly melt and synthesize an intermediate V-Ta-Mo under an argon atmosphere for 5 times, and then the remaining elements are added to the intermediate, and the melting is repeated for 5 times under an argon atmosphere to obtain the target alloy HEV5 of this embodiment, i.e., V 0.901 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.019 .
[0078] The model diagram of the crystal structure of the vanadium-based neutron-transparent alloy prepared in Examples 1 to 12 is as follows: Figure 1 As shown, V atoms and M atoms are randomly distributed at the vertices and center of the body-centered cubic lattice. V and M atoms are completely disordered, occupying the same Wyckoff position 2a, and the atomic coordinates are (0,0,0).
[0079] Figure 2 The vanadium-based neutron-transparent alloy round ingots prepared in Examples 1 to 6 are shown. It can be seen that the surface is smooth and the appearance is uniform. The size is about 60 mm in diameter and about 8 mm in height.
[0080] Figure 3 , Figure 4 ,and Figure 5 The XRD spectra of the products of Examples 1 to 6 and Examples 7 to 12 are respectively used to detect the alloy phase. The test conditions are: using the Bragg-Brentano mode, CuKα radiation (wavelength ), the test angle range is 10-115°, the step length is 0.01°, and the single data collection time is 36min. The XRD test results show that the vanadium-based neutron transparent alloy prepared by the present invention is composed of a single phase, all diffraction peaks are fitted with the model, V and M atoms form a disordered solid solution structure of body-centered cubic structure, and V and M atoms are randomly distributed at the vertices and body center of the body-centered cubic lattice, the space group is Im-3m, and the test results are consistent with Figure 1 is consistent with the model.
[0081] Figure 6 and Figure 7 The high-resolution neutron diffraction patterns of the products of Examples 1 to 6 and Examples 7 to 12 respectively show that there are no obvious Bragg diffraction peaks in the entire 2θ range for the 12 alloy systems prepared, and the spectrum backgrounds are very clean, which indicates the chemical short-range order in the alloy structure, and the dopant is located at the same 2a site as V, which further proves the neutron transparency property of the alloy of the present invention.
[0082] like Figure 8 As shown in Figure 2, except for the V-Al system, the unit cell parameters of the samples increase to a small extent with the increase of the dopant atomic size. The symmetry of the lowest index peaks (110) and (200) of the products of Examples 1 to 6 was analyzed by synchrotron monochromatic X-ray with a monochromatic wavelength. The peak heights of each system were symmetrical and no shoulders were observed. The analysis results of Examples 7 to 12 are as follows: Fig. 9 As shown, all samples have better resolution for the (110) and (200) peaks, and these two characteristic peaks are highly symmetrical.
[0083] Fig.10 and Fig.11 They are optical microscope images of the alloys prepared in Examples 1 to 6 and Examples 7 to 12 at 1000 times magnification, respectively. The red scale line represents a length of 10 μm. In general, the doping clustering is not obvious in each alloy system, and only a few special surface features at the micron size can be observed in the optical microscope image of the V-Mo sample.
[0084] See also Fig.12 and Fig.13 , through small-angle neutron scattering detection, it was further confirmed that the prepared samples had no doping segregation in the range of 1 to 120 nm. The transparent properties of bulk neutrons and the situation of doping clusters were analyzed from the mesoscopic scale. For larger q regions, the data points of all samples were basically flat, which indicates that no mesoscopic-sized objects were observed and all samples were uniform without doping segregation.
[0085] In order to further explore the potential applications of alloy materials, the present invention also conducts the following in-depth analysis on the stability and mechanical properties of the materials.
[0086] First, TGA / DSC was used to study the oxidation reaction of the alloy in an O2 atmosphere. When metal V is oxidized to V2O5, its weight percentage will theoretically increase by 78.72%. Metal dopants may be oxidized to M2O3 (e.g., Al, Fe), MO (e.g., Ni), M2O5 (e.g., MO, Ta, and Nb), and MO2 (e.g., Sn). Therefore, the final weight of the alloys of each example after complete oxidation must be slightly different from the theoretical value. See Fig.14 Thermogravimetric analysis results show that all alloys of Examples 1 to 6 maintain stable quality after 800°C. Intermediate products of about 130% and 150% by weight are observed at around 600°C and 700°C, respectively, due to the formation of VO and V2O3 during the oxidation process. Surprisingly, the first oxidation state of the alloys of Examples 1 to 6 is suppressed, and the phase transition temperature is about 630°C, which is far beyond the limit temperature reported in the prior art. This test result shows that the alloys of Examples 1 to 6 are similar to vanadium metal and existing Ti 2.08 Compared with Zr alloys, single element doped V-based alloys have better chemical stability.
[0087] Furthermore, TGA / DCS analysis was performed on the HEV1 sample of Example 7 to explore the chemical stability of the multi-element doped neutron transparent alloy under high temperature of O2. Fig.15 , with the increase of temperature, the alloy weight percentage increases, such as Fig.15 a and Fig.15 As shown in Figure 2, the weight increase is directly related to the oxidation reaction of vanadium and dopants. The HEV1 sample of Example 7 conforms to the general trend of high-temperature oxidation behavior. However, the start temperature of the oxidation reaction of most alloys is about 625°C. Fig.15 As shown in c, HEV1 composed of V, Ta, Nb, Al, Fe and Sn only undergoes in-situ oxidation reaction at about 640°C, which is about 15°C higher than other binary V-based alloys. This shows that multi-element dopants have a synergistic effect on the performance of zero-based alloys.
[0088] As mentioned above, the existing Ti 2.08 The insufficient mechanical strength of Zr neutron transparent alloy leads to limited application of the material. Fig.16 The standard dumbbell shape shown in the figure is stretched horizontally at room temperature until the tensile "fracture point" is observed, and the engineering strain-stress characteristic curve of the material is obtained to analyze and evaluate the mechanical properties of the material. Fig.17 As shown, below 250 MPa, all alloys of Examples 1 to 6 experienced an elastic region, while the stress levels of different alloys varied greatly between 250 and 425 MPa. Taking the V-Nb sample as an example, at a maximum stress level of 425 MPa, the elongation was about 20%, while for the V-Mo sample, at a maximum stress level of about 260 MPa, the elongation was only about 1%. It can be seen that Nb-doped V-based alloys exhibit excellent chemical and mechanical properties and are expected to be used in the development of advanced in-situ devices and high-temperature / high-pressure neutron scattering sample holders for neutron diffraction and total scattering measurements.
[0089] like Fig.18As shown, all samples of Examples 7 to 12 exhibited large mechanical yield and good elastic deformation characteristics, that is, the samples were not easily deformed before the breaking point. 0.902 Nb 0.018 Ta 0.035 Fe 0.008 Sn 0.026 Mo 0.019 ) has the largest mechanical yield, and the mechanical stress is about 400MPa, which is much higher than the binary system alloy of Examples 1-6.
[0090] In summary, the present invention has prepared a variety of vanadium-based neutron transparent alloys through a vacuum arc melting process, which has low energy consumption, easy control of synthesis process conditions, wide application range, and the obtained vanadium-based neutron transparent alloy ingot has uniform microstructure. These materials do not produce Bragg diffraction peaks, and their neutron transparency is verified by neutron diffraction patterns, which not only broadens the range of raw material selection for neutron transparent alloys, but also can effectively reduce costs. At the same time, the diversity of alloy constituent elements provides more possibilities for regulating the physical properties of vanadium-based neutron transparent alloys, and can produce non-magnetic neutron scattering sample boxes such as V-Al, V-Nb, V-Ta, V-Sn, and V-Mo.
[0091] More importantly, the present invention pioneered a multi-element doped V-based neutron transparent alloy, which is composed of 5 doping elements. The results of high-resolution neutron diffraction and X-ray diffraction analysis show that the dopant is uniformly distributed at the 2a site of the Im-3m structure of V, and X-ray pair distribution analysis (PDF) and small-angle neutron scattering (SANS) prove that there are no chemical clusters in the material. Based on the chemical oxidation analysis of HEV and single-dopant V-based alloys to O2 at high temperatures, the HEV alloy is more chemically stable than any single-dopant V-based alloy. In addition, HEV4 composed of V, Ta, Nb, Fe, Sn and Mo has the most outstanding engineering yield properties. Therefore, the multi-element doped alloy of the present invention has a synergistic effect in improving the performance of neutron transparent materials, and the chemical stability and mechanical properties of Examples 7 to 12 are further improved compared with Examples 1 to 6.
[0092] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A vanadium-based neutron-transparent alloy, characterized in that: The alloy is a disordered solid solution of a body-centered cubic structure composed of a single crystal phase, with a space group of Im to 3m and a chemical composition of V 1-x M x , x<0.1, wherein V is the metal element vanadium, and M is selected from one or more of Al, Nb, Ta, Fe, Sn or Mo.
2. A vanadium-based neutron-transparent alloy according to claim 1, characterized in that: The neutron diffraction spectrum of the alloy has no Bragg diffraction peak between 50° and 160°.
3. The vanadium-based neutron-transparent alloy according to claim 1, characterized in that: All metal atoms in the vanadium-based neutron transparent alloy are randomly distributed at the same Wyckoff site.
4. The vanadium-based neutron-transparent alloy according to claim 1, characterized in that: The neutron transparent alloy is composed of two elements, and the chemical formula is: V 0.9002 Al 0.0998 、V 0.9486 Nb 0.0514 、V 0.9476 Ta 0.0524 、V 0.9611 Fe 0.0389 、V 0.9421 Sn 0.0579 or V 0.946Im o 0.0539 .
5. The vanadium-based neutron-transparent alloy according to claim 1, characterized in that: The neutron transparent alloy is composed of multiple elements, and the chemical formula is: V 0.902 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 、V 0.908 Nb 0.018 Ta 0.036 Al 0.01 Fe 0.008 Mo 0.02 、V 0.892 Nb 0.018 Ta 0.035 Al 0.001 Sn 0.026 Mo 0.019 、V 0.902 Nb 0.018 Ta 0.035 Fe 0.008 Sn 0.026 Mo 0.019 、V 0.917 Nb 0.018 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.02 or V 0.901 Ta 0.036 Al 0.01 Fe 0.008 Sn 0.026 Mo 0.019 .
6. The vanadium-based neutron-transparent alloy according to claim 5, characterized in that: The in-situ oxidation reaction temperature of the alloy reaches above 640°C.
7. The method for preparing a vanadium-based neutron-transparent alloy according to any one of claims 1 to 6, characterized in that: The steps include: S1. Design the formula of vanadium-based neutron-transparent alloy; S2, weighing and mixing: according to the vanadium-based neutron transparent alloy formula designed in step S1, weigh the weight of metal V and metal M to obtain a vanadium-based neutron transparent alloy raw material; S3, vacuum melting: using a primary or secondary melting process at 3000 ~ 3500 ℃, protective atmosphere environment to produce alloy ingots; S4. Processing: The alloy ingot is processed to a suitable size by wire cutting and polished to a smooth surface.
8. The method for preparing a vanadium-based neutron-transparent alloy according to claim 7, characterized in that: The protective atmosphere is argon.
9. The method for preparing a vanadium-based neutron-transparent alloy according to claim 7, characterized in that: The alloy is composed of two elements and the metal M is selected from Fe, Nb, Ta or Mo. A neutron transparent alloy ingot is prepared through a one-step smelting process.
10. The method for preparing a vanadium-based neutron-transparent alloy according to claim 7, characterized in that: The alloy is composed of two elements and the metal M is selected as Al or Sn, or the alloy is composed of multiple elements and is prepared by a two-step smelting process, firstly using part of the ingredients for partial pre-melting to form a stable intermediate product, and then melting it with the remaining raw materials to obtain a neutron-transparent alloy ingot of the target composition.
Citation Information
Patent Citations
Molybdenum-titanium alloy neutron transparent material and preparation method thereof
CN105779819A
Vanadium nickel alloy for preparing neutron scattering experimental sample box and application thereof
CN106290425A
High-strength titanium-zirconium alloy neutron transparent material and preparation method thereof
CN115354191A
Cited By
Anti-oxidation zero-coherence scattering alloy with BCC structure and preparation method of anti-oxidation zero-coherence scattering alloy
CN120555853A
A BCC structure, an oxidation-resistant zero-coherence scattering alloy and its preparation method
CN120555853B